Inconsistency evaluation of vehicle-oriented fuel cell stacks based on electrochemical impedance under dynamic operating conditions. (15th February 2023) - Zhao, Lei; Yuan, Hao; Xie, Jiaping; Jiang, Shangfeng; Wei, Xuezhe; Tang, Wei; Ming, Pingwen; Dai, Haifeng
Abstract: The dynamic inconsistency performance of the proton exchange membrane fuel cell stack is a crucial indicator for vehicular applications. This paper comprehensively studies for the first time the local dynamic inconsistency of a high-power fuel cell stack with 30 kW rated power based on impedance. The stack is divided into ten groups equally. First, each polarization process and frequency impedance under different working conditions is quantitatively analyzed by the equivalent circuit model combined with the relaxation time distribution. It is determined that 1 Hz, 50 Hz, and 2500 Hz impedance can describe the oxygen transport, charge transfer, and ohmic variation trends, respectively. Then, the effects of loads, air stoichiometry, backpressure, operating temperature, and cathode humidity on in-stack dynamic inconsistency response are evaluated from an internal dynamics perspective. The results show that the local dynamic inconsistent responses in the fuel cell stack depend mainly on the oxygen transfer capacity. Oxygen transport affects the difference in local voltage transient drop after a current step and the inconsistency voltage recovery. These works provide an in-depth understanding of the differences in the dynamic response of high-power fuel cell stacks, which has an important implication for system control and structural design optimization. Graphical abstract: Image 1 Highlights: The characteristic impedance of a 30 kW stack throughout ten equal areas is measured. The fixed frequencies related to each polarization process are quantitatively analyzed. Impedance-based in-stack inconsistency under dynamic vehicular conditions is evaluated. The polarization dynamics difference under voltage inconsistency response is revealed. Application prospects and feasibility of multi-channel local impedance are discussed.